2022
DOI: 10.3390/ijerph19053083
|View full text |Cite
|
Sign up to set email alerts
|

Access to Healthcare and Social Protection among Migrant Workers in Thailand before and during COVID-19 Era: A Qualitative Study

Abstract: Thailand is a popular host nation for international migrant workers, particularly those from Cambodia, Lao PDR, and Myanmar. Thailand has introduced approaches to protect their rights for health and social welfare, using various mechanisms over many years. However, the implementation of these policies is dynamic and has been influenced by national security, economic necessity, and public health concerns. The aim of this study was to explore how Thailand designs and implements health and social welfare policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…A Qualitative Study assessed access to health services among migrant workers in Thailand during the COVID-19 era [Kunpeuk et al, 2022]. An improved health system design and intersectoral policy coherence were considered important.…”
Section: Discussionmentioning
confidence: 99%
“…A Qualitative Study assessed access to health services among migrant workers in Thailand during the COVID-19 era [Kunpeuk et al, 2022]. An improved health system design and intersectoral policy coherence were considered important.…”
Section: Discussionmentioning
confidence: 99%
“…29,30,34,42,46,47,61,69,70 Subtheme 1.5: Opportunity for advancing equity and justice A major benefit of PSD methods discussed in several articles within this review was the opportunity to advance health equity. 25,28,29,31,[34][35][36]38,42,44,45,47,53,[57][58][59][60][61][69][70][71][72][73][74][75] PSD methods facilitate equity by allowing a diverse set of stakeholders to provide expertise to inform a model and necessarily include the engagement and participation of stakeholders with proximity to the issue being investigated. Community-based system dynamics, a specific approach under the umbrella of PSD, explicitly includes directly impacted populations in the modeling process to combat epistemic violence and imbue the problem-structuring and theory-building processes with perspectives that have historically been excluded from the scientific process.…”
Section: Family and Community Healthmentioning
confidence: 99%
“…A major benefit of PSD methods discussed in several articles within this review was the opportunity to advance health equity 25,28,29,31,34–36,38,42,44,45,47,53,57–61,69–75. PSD methods facilitate equity by allowing a diverse set of stakeholders to provide expertise to inform a model and necessarily include the engagement and participation of stakeholders with proximity to the issue being investigated.…”
Section: Themes and Subthemesmentioning
confidence: 99%
“…The Thai government also failed to implement inclusive policies that ensured migrant workers had reliable access to social protection and healthcare, while also failing to provide adequate living conditions. In a study that interviewed migrant workers in Thailand, Kunpeuk et al ( 2022 ) found that many migrant workers did not have access to social or health services and were in overcrowded living conditions. They found that migrant workers in Thailand were “disproportionately affected by COVID-19” (Kunpeuk et al 2022 p. 11).…”
Section: Case Description Per Country: Thailand Italy and Canadamentioning
confidence: 99%
“…In a study that interviewed migrant workers in Thailand, Kunpeuk et al ( 2022 ) found that many migrant workers did not have access to social or health services and were in overcrowded living conditions. They found that migrant workers in Thailand were “disproportionately affected by COVID-19” (Kunpeuk et al 2022 p. 11). For Thailand to reduce irregular migration, effort must be invested to reduce the burdens and costs migrants face when attempting to work in Thailand as well as create more inclusive policies and access to social and health security for migrants.…”
Section: Case Description Per Country: Thailand Italy and Canadamentioning
confidence: 99%